Failure of propranolol to improve exercise tolerance in patients with mitral stenosis in sinus rhythm. Issue 3 (September 1987) - Bassan, M M; Michaeli, J; Shalev, O
Abstract : Propranolol reduces left atrial pressure at rest and during exercise in patients with mitral stenosis by lowering cardiac output and heart rate. Ten patients (aged 19-56) with moderate to severe isolated mitral stenosis were studied to determine whether propranolol increased their exercise tolerance. All were in sinus rhythm and free of left or right ventricular failure. Patients were trained in an individually graded bicycle or treadmill exercise protocol that provoked a reproducible degree of near maximal dyspnoea during the second three minute stage of exercise. Propranolol (80 mg or 120 mg) or matching placebo in two or three divided daily doses was given for one week in random double blind fashion. Exercise testing and questioning about subjective clinical response were carried out at the end of each week by an investigator who was unaware of the patient's heart rate. During propranolol treatment the heart rate was 19 beats/minute slower at rest and 38 beats/minute slower at peak exercise, but there was no change in mean exercise time to dyspnoea (274 s during propranolol vs 283 s during placebo). Four patients felt worse during the propranolol week, one patient felt better during the propranolol week, and five patients felt no difference between the two weeks. Propranolol did not improve objective or subjective exercise tolerance in patients with isolated mitral stenosis in sinus rhythm.